Spenser's Colin Clout : an introductory study - Brown, Molly Anne (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1985)
From introduction: In the sixth book of The Faerie Qveene, the reader is presented with a vision of the Graces and their attendants dancing on Mount Acidale to the piping of a simple shepherd. Spenser identifies this favoured musician as Colin Clout and then goes on to pose a seemingly inconsequential rhetorical question. "Who knowes not Colin Cloute?" he asks. The note of confident pride which can be discerned in the query clearly reveals Spenser's peculiar interest in one of his most intriguing creations. It is almost impossible to read a representative selection of Spenser's poetical works without noticing the hauntingly frequent appearances of his "Southerne shepheardes boye". Colin appears or is named in no fewer than six of Spenser's poems.
Keywords: Spenser, Edmund, 1552?-1599 -- Criticism and interpretation; Faerie Queene; English poetry; Epic; Criticism; Interpretation; Clout, Colin (Fictitious character)